Friction and Wear Measurements with an Adapted Ball-On-Pyramid Test Setup - Viktor Krasmik (Japanese Society of Tribologists, 2016)
In tribological testing with simplified test geometries, the contact configurations usually consist of two bodies representing one material pairing. This contribution introduces an adapted ball-on-pyramid test configuration which allows the experimental investigation of combined contact configurations consisting of more than one material pairing. In the proposed test setup, a ball is loaded against four flat test samples positioned in a pyramid-like sample holder with an opening angle of 90°. The test samples are arranged on the circumference in a regular manner. The ball rotates uniformly around its vertical axis and slides over the samples. The coefficient of friction, the running-in wear, the linear wear rate, the wear scar diameter, and the weight loss of four different sample materials and their combinations are compared and discussed. The obtained results for combined contact configurations with more than one material pairing show that a manipulation of the friction and wear characteristics is possible.